Pendampingan Membaca Al-Quran Menggunakan Metode Ummi pada Mahasiswa Teknik Informatika di STT Wastukancana Purwakarta - Megawati, Irma; Mukti, Saepul; Setiawan, Usep; Narkum, Narkum; Ahmadiah, Didih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Ummi method can lead students and female students to be able to read the Al-Quran well and correctly according to the tajwid, in reality the underlying problems are low activity in studying the Al-Quran, lack of motivation to learn the Al-Quran, non-varied learning methods and models, and ability. reading the Koran is still lacking. In this community service activity, the author wants to research the extent to which female students read the Koran by carrying out various methods including: Lectures, questions and answers and demonstrations on the practice of reading the Koran. This technique is used to make it easier for female students to read and practice the Al-Quran, especially in family, school and community environments. The ummi method is one method of studying the Koran. Ummi itself means Mother, who remains patient and gentle. And you can invite all students from the LDK (Student Da'wah Institute) informatics engineering study program at STT Wastukancana to learn to read the Koran using the Ummi method. Easily, quickly and according to the tajwid. This ummi method is starting to motivate female students because the method is easy, fun and calms the hearts of the readers. After learning the Koran using the Ummi method, it is easy for students to memorize wherever they are, of course it will be easy to remember.